Theoretical and practical support service for sports elite: foreign experience - Zubkova, A. V.; Abalyan, A. G.; Dolmatova, T. V.; Fomichenko, T. G.; Shestakov, M. P. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to run a comparative analysis of the theoretical and practical support service to foreign sports elites.